A unique algorithm for the determination of peptide-carrier protein conjugation ratio by amino acid analysis using intrinsic internal standard. Issue 29 (15th June 2020) - Yang, Gengcheng J.; Yang, Yanhong; Shaddeau, Andrew; Cai, Cindy X.; Li, Yile; Gulla, Krishana; Zhang, Yaqiu; Ou, Li; Cooper, Jonathan W.; Lei, Q. Paula
Highlights: A new algorithm to calculate peptide-carrier protein conjugate ratio An intrinsic amino acid application to minimize the assay variability The optimized method was applied to various FP-rTTHc conjugate candidates Abstract: An N-terminal peptide of the HIV-1 fusion peptide (FP) with eight amino acid residues (FP8) was conjugated to a recombinant Tetanus Toxoid Heavy Chain Fragment C (rTTHc) as a carrier protein to help boosting immunogenicity against HIV-1. In this rapid communication, a unique algorithm to determine FP-rTTHc conjugation ratio was developed based off the amino acid analysis. Five well recovered amino acids (present in both FP and rTTHc) were used to calculate the conjugation ratio, while proline (present only in rTTHc) was identified and utilized as the intrinsic internal standard for normalization. With this calculation, the assay variability was minimized (<20%), especially for conjugates with moderate to low conjugation ratios as being compared to previously reported methods. The approach offers a reliable tool to determine the efficiency of the conjugation reactions for in-process monitoring and for final conjugate product characterization.